IMPROVING STUDENTS’ READING COMPREHENSION THROUGH QUESTION-AND-ANSWER RELATIONSHIP (QAR) AT MAN 2 KOTA MAKASSAR - Fatmiah Utami, Andi Rachma; Salija, Kisman; Sultan, Sultan (JTechLP: Journal of Technology in Language Pedagogy, 2022)
This study is a pre-experimental research that aims to find out the use of Question-and- Answer Relationship (QAR) to improve students’ reading comprehension ability. The participants were the students of XI MIPA 1 MAN 2 Kota Makassar for the academic year 2021/2022 with as many as forty-four students. Cluster random sampling was used as the way of selecting the sample and a reading test was administered as the way of collecting data. The result showed that the score of students’ reading comprehension tests were increasing after conducting QAR in the reading class. The mean score of students’ reading comprehension test before and after applying the QAR strategy improved by 35.96%. This means that the students’ reading comprehension ability can be improved by using Question and Answer Relationships as a teaching strategy in reading class.